Deaf empowerment : emergence, struggle, and rhetoric - Jankowski, Katherine A. (Gallaudet University Press, 1997)
Deaf Empowerment examines the Deaf social movement in America from its inception in the mid-19th century through its growth and empowerment in the late 20th century. Jankowski traces how Deaf advocates adopted tactics from the civil rights movement, the movement for women's rights, and other social revolutions to achieve their goals.